Ballymoon Castle: Co Carlow: South East. Aspt. July 29th 1792 - Grose, Daniel, approximately 1766-1838; Cocking, Thomas, fl. ca. 1783-1791 (1792)
South East view of Ballymoon Castle, County Carlow, Ireland, with a man and woman chatting in the foreground.
Engraved as Plate 4 in Volume 2 of "Antiquities of Ireland" by Francis Grose and published by Samuel Hooper, High Holborn, London, 1794.
Inscribed in ink on verso of drawing: Reduced by T. Cocking.
Title inscribed in ink u.c. on verso of drawing.
Watermark visible u.c..
Attributed to Lieutenant Daniel Grose, (ca. 1766-1838).
Keywords: Ballymoon Castle (Carlow, Ireland) -- 1790-1800.; Castles & palaces -- Ireland -- Carlow -- 1790-1800.; Ink drawings -- Irish -- 1790-1800.; Wash drawings -- Irish -- 1790-1800.